Qualitative Content Analysis of Education Digital Literacy in Nitijana Game - Syarifah Nur Aini (Informasi, 2025)
The massive spread of narratives tied to emotional constructs such as threats and hatred has brought about destructive impacts on society. There is a growing need to enhance knowledge and skills in media engagement, particularly in responding to circulating information. Digital literacy has become a crucial aspect that must be improved by the information society. Through an education-entertainment approach, Nitijana emerges as a medium for digital literacy education in the form of a game. This study examines the digital literacy elements presented in the Nitijana game through qualitative content analysis. The analysis draws on Japelidi's components of digital literacy, Schell's game development framework, and the concept of cyberspace to dissect this phenomenon. Users are able to play the game while simultaneously learning and practicing various aspects of digital literacy, such as fact-checking hoaxes and verifying information. The findings of this research reveal several aspects of digital literacy, including access, selection, comprehension, analysis, verification, evaluation, participation, and distribution. Meanwhile, the fundamental elements found in the Nitijana game include its mechanics, storyline, and aesthetics. It is hoped that this article will contribute to the field of communication science, particularly in the areas of entertainment media and digital literacy.